Call based enquiry for COVID-19 vaccine (Covishield) adverse events in a tertiary care government hospital in India - Priya, Adity; Gupta, Pratibha; Kumar, Vijay; Srivastava, Salil Kumar; Yadav, Yogesh Kumar; Srivastava, Arshita (International Journal Of Community Medicine And Public Health, 2022)
Background: Vaccination is one of the crucial intervention to fight against the ongoing COVID-19 pandemic. The ongoing vaccination drive aims for achieving national vaccination coverage. Due to the expedited roll out of COVID-19 vaccine, there has been a fear and concern regarding its safety. The present study aims to enquire actively about the adverse events after COVID-19 vaccination and disseminate this information to the public to promote vaccine acceptance. Methods: A call based active enquiry was done to know the frequency and severity of various adverse events among the recipients of COVID-19 vaccine’s Covishield (SII-ChAdOx1 nCoV-19) first dose. Call based enquiry was done for local as well as systemic adverse events on day 1, 3 and 7 of vaccination. Results: Out of the total of 1201 who responded to calls on all three days, 766 (63.7%) of them had at least one of the adverse event. There were only 4 (0.33) recipients who had severe/serious events. The most frequent systemic and local AEFI reported was body ache/ malaise and pain at injection site in 309 (25.7%) and 664 (55.3%) participants respectively. Most of the AEFI’s improved over a week with only 17 (1.4%) participants reporting persistence of any adverse event on day 7 of vaccination. Conclusion: Our study can provide scoping base for development of a proper surveillance program to monitor the AEFI by ‘active’ query and use of a call-based system especially for novel vaccines.